O aprendizado em saúde mental durante as diferentes etapas da graduação de medicina: uma narrativa crítico-reflexiva - Ilhesca, Milena Sandri (Universidade Federal de São Carlos)
This paper presents a critical-reflective analysis of the author's medical degree from 2020 to 2025, from the perspective of her experiences with the topic of mental health. The methodology for this work is based on a qualitative analysis of documentary records developed by the author throughout her undergraduate studies. The results, presented in narrative form, highlight the importance of the subject in question and its application across the different undergraduate cycles. They also address the impact of the COVID-19 pandemic - which the author experienced throughout her undergraduate studies - on her desire to delve deeper into the subject. Finally, it explains how these lessons were incorporated into the author's professional practice and personal life, highlighting the impact of the topic beyond the medical field.
Learning about mental health during different stages of medical school: a critical-reflexive narrative
Keywords: Medicina; Saúde mental; Narrativa; CIENCIAS DA SAUDE; 3. Saúde e Bem-Estar